2019
DOI: 10.1186/s12909-019-1539-5
|View full text |Cite
|
Sign up to set email alerts
|

Student motivation to learn: is self-belief the key to transition and first year performance in an undergraduate health professions program?

Abstract: Background Student motivation to learn has been undervalued to date though has been identified as an area influencing student success and retention at university. The transition into university has been highlighted as a key period affecting student outcomes as well as well-being. Early identification of those students at risk may assist the transition for many students moving into higher education. Previous research has identified the Motivation and Engagement Scale – University/College (MES-UC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 41 publications
2
40
0
4
Order By: Relevance
“…Moreover, we identified that resilience and intrinsic motivation were significant predictors of self-compassion, echoing previous findings: students who are able to bounce back from difficulties (i.e., resilience) and are passionate about their studies (i.e., intrinsic motivation) tend to have higher levels of kindness towards themselves [83,91,92]. In a recent study by Edgar et al [93], student success is influenced by self-belief, which has been identified as a key dimension of motivation. Future work may be useful to investigate particular aspects of self-belief because research indicates it has a significant influence on motivation and resilience [94], which can impact self-compassion.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, we identified that resilience and intrinsic motivation were significant predictors of self-compassion, echoing previous findings: students who are able to bounce back from difficulties (i.e., resilience) and are passionate about their studies (i.e., intrinsic motivation) tend to have higher levels of kindness towards themselves [83,91,92]. In a recent study by Edgar et al [93], student success is influenced by self-belief, which has been identified as a key dimension of motivation. Future work may be useful to investigate particular aspects of self-belief because research indicates it has a significant influence on motivation and resilience [94], which can impact self-compassion.…”
Section: Discussionsupporting
confidence: 88%
“…Positive and significant inverse associations were found between the Performance-avoidance Goal domain and the variables school performance and self-perceived health, reinforcing the evidence from a study carried out with university students in Australia, which showed that intrinsic motivation and self-confidence for learning can improve the students' success in their academic trajectory and their psychosocial well-being (22) . Student who avoid situations that may favor knowledge acquisition tend to show a lack of confidence in themselves, low self-esteem, and psychological conditions that impair their ability to achieve individually and contribute to the group.…”
Section: Discussionsupporting
confidence: 75%
“…Being able to identify the key dimensions that influence student success in the first year at university will be useful to improvements in curriculum, teaching and learning practices and conditions for students. Undertaking measures to enhance academic motivation, for example, can include changing curriculum based on student motivation or by targeting early those students with reduced self-belief (Edgar et al, 2019). Universities in Vietnam should take into account factors such as interior environment and academic learning space so as to positively promote students' learning.…”
Section: Resultsmentioning
confidence: 99%